Transperineal ultrasound as a reliable tool in the assessment of membranous urethra length in radical prostatectomy patients - Kania Piotr (Nature Portfolio, 2021)
Abstract To evaluate the usefulness of transperineal ultrasound (TPUS) as a method of membranous urethra length (MUL) measurement and investigate whether preoperative (MULpre) and postoperative (MULpost) would be associated with the degree and time of urinary continence recovery after laparoscopic radical prostatectomy (LRP). 84 patients who underwent LRP between January 2017 and December 2018 were selected for final analysis. All patients had preoperative and postoperative measurement of MUL in TPUS. Urinary continence was defined as no pad or a safety pad. Recovery of continence was assessed at 1, 3, 6 and 12 months after catheter removal. We prospectively analyzed correlation of MULpre, MULpost and a percent change in membranous urethral length (MULratio) with the urinary continence status. 69 (82%) patients regained continence in the follow-up of 12 months. MULpre, MULpost and MULratio assessed in TPUS were larger in subgroups of patients who regained continence earlier and in the entire continent group. Spearman rank test showed strong correlations between MULpost and MULratio (R—0.6 and R—0.56, respectively, p < 0.0001) with the time to continence recovery in the cumulative 12 months follow-up. TPUS allowed a reliable measurement of MUL before and after LRP. MULpre, MULpost as well as MULratio are related with time to regain continence and recovery rate after LRP. Sparing longest possible sphincteric urethra, with respect to oncological outcomes is a key factor in recovering continence after prostate cancer surgery.